Juridical and Economic Analysis of Profit Margin Discounts in Murabahah Financing Early Settlement - Habibah, Septiara Nur; Pertiwi, Dian; Arianti, Farida (Institut Agama Islam Negeri Batusangkar, 2024)
The purpose of this study is to explain the implementation of profit margin discounts at BSI KC Bukittinggi Sudirman 1 concerning DSN MUI Fatwa No. 23/DSN-MUI/III/2002 on Discounts for Early Settlement in Murabahah and DSN MUI Fatwa No. 153/DSN-MUI/VI/2022 on Early Settlement of Murabahah Financing Debt. This research is field research with a qualitative approach. Data were collected using interview and documentation techniques. The research explores how the implementation of profit margin discounts in the early settlement of Murabahah financing is carried out at BSI KC Bukittinggi Sudirman 1, how BSI KC Bukittinggi Sudirman 1 responds to DSN MUI Fatwa No. 153/DSN-MUI/VI/2022 on Early Settlement of Murabahah Financing Debt, and what impacts arise from the implementation of DSN MUI Fatwa No. 153/DSN-MUI/VI/2022 on the practice of profit margin discounts at BSI KC Bukittinggi Sudirman 1. This study finds that the implementation of profit margin discounts in early settlement of Murabahah financing, as governed by DSN MUI Fatwa No. 23/DSN-MUI/III/2002 on Discounts for Early Settlement in Murabahah, differs from the implementation under DSN MUI Fatwa No. 153/DSN-MUI/VI/2022 on Early Settlement of Murabahah Financing Debt. Initially, the profit margin discount was permitted but became mandatory following the issuance of the second fatwa. BSI KC Bukittinggi Sudirman 1 responded positively to the second fatwa, although several impacts arose from its implementation based on DSN MUI Fatwa No. 153/DSN-MUI/VI/2022 on Early Settlement of Murabahah Financing Debt.